Quiescent galaxies in a virialized cluster at redshift 2: evidence for accelerated size growth. Issue 4 (2nd September 2021) - Noordeh, E; Canning, R E A; Willis, J P; Allen, S W; Mantz, A; Stanford, S A; Brammer, G
ABSTRACT: We present an analysis of the galaxy population in XLSSC 122, an X-ray-selected, virialized cluster at redshift z = 1.98. We utilize Hubble Space Telescope (HST) Wide Field Camera 3 (WFC3) photometry to characterize the activity and morphology of spectroscopically confirmed cluster members. The quiescent fraction is found to be $88^{+4}_{-20}$ per cent within 0.5 r 500, significantly enhanced over the field value of $20^{+2}_{-2}$ per cent at z ∼ 2. We find an excess of 'bulge-like' quiescent cluster members with Sérsic index n > 2 relative to the field. These galaxies are found to be larger than their field counterparts at 99.6 per cent confidence, being on average $63^{+31}_{-24}$ per cent larger at a fixed mass of $M_\star = 5× 10^{10} \, M_\odot$ . This suggests that these cluster member galaxies have experienced an accelerated size evolution relative to the field at z > 2. We discuss minor mergers as a possible mechanism underlying this disproportionate size growth.